Effect of the addition of green mussel shell nanochitosan on the hardness of glass ionomer cement: Experimental study - Widyastuti, Noor Hafida; Ningsih, Juwita Raditya; Yuletnawati, Sartari Entin; Dewi, Listiana Masyita; Jayanti, Puji Tri (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2024)
Introduction: Treatment of caries can be carried out through restoration. The selection of restorative materials in dentistry highly considers hardness to withstand occlusal loads. Glass Ionomer Cement is one substance that can be utilized for restoration. By including chitosan derived from green mussel shells, GIC insufficiency is remedied. It is processed into nanochitosan since its usage is maximized when it is manufactured in nanoscale. This study aims to analyze the effect of adding green mussel shell nanochitosan on the hardness of glass ionomer cement. Methods: This study used a posttest-only control group design in a laboratory setting. Six groups are formed from the group. First, as a control group (GIC Control), GIC was made without the addition of nanochitosan. The GIC liquid was supplemented with nanochitosan at four distinct concentrations: 0.5%, 1%, 1.5%, and 2%, to create the GIC group with the addition of nanochitosan. A Vickers microhardness tester was used to test the surface hardness. HV0.05 (490.3 mN) was the load employed in this study, and the indentation time was set at two seconds. The sample has an 8 mm thickness and a box-like form. Every sample was indented twice. Results: The GIC hardness test with no additives had a mean result and standard deviation of 31.94 ± 3.54. The hardness value of glass ionomer cement can be increased by nanochitosan, with the average outcomes and standard deviation as follow: Concentration: 1.5% = 95.22 ± 14.12, 1% = 91.20 ± 15.09, 2% = 117.60 ± 40.90, and 0.5% = 51.60 ± 9.34. The One-Way Anova test showed a significant difference between the concentration groups in the hardness value of glass ionomer cement, with p = 0.000, meaning that p <0.5. Conclusion: The addition of green mussel shell nanochitosan can increase the hardness of glass ionomer cement.Pengaruh penambahan nanokitosan cangkang kerang hijau terhadap kekerasan semen ionomer kaca: studi eksperimentalABSTRAKPendahuluan: Penanganan karies dapat dilakukan dengan cara restorasi. Pemilihan bahan restorasi di kedokteran gigi sangat mempertimbangkan kekerasan untuk menahan beban oklusal. Salah satu bahan yang bisa digunakan untuk restorasi adalah Semen Ionomer Kaca(SIK). Kekurangan SIK diatasi dengan cara mencambahkan kitosan yang didapat dalam cangkang kerang hijau. Penggunaannya lebih efektif apabila dibuat dalam ukuran nano, sehingga diolah menjadi nanokitosan. Penelitian ini bertujuan untuk menganalisis pengaruh penambahan nanokitosan cangkang kerang hijau terhadap kekerasan semen ionomer kaca. Metode: Penelitian ini merupakan penelitian laboratorium dengan menggunakan desain penelitian posttest only control group design. Kelompok terbagi menjadi 6 kelompok. Pertama, SIK disiapkan tanpa penambahan nanokitosan sebagai kelompok kontrol (SIK Kontrol). Kelompok SIK dengan penambahan nanokitosan dibuat dengan menambahkan nanokitosan ke dalam cairan SIK dengan empat konsentrasi berbeda, yaitu 0,5%, 1%, 1.5%, dan 2%. Pengujian kekerasan permukaan dilakukan menggunakan alat Vickers microhardness tester. Beban yang digunakan pada penelitian ini yaitu HV0,05 (490,3mN) dengan lama indentasi yaitu 2 detik. Bentuk sampel berbentuk kotak dengan ketebalan 8 mm. Setiap sampel dilakukan indentasi sebesar 2 kali Hasil: Hasil rerata dan standar deviasi uji kekerasan SIK tanpa penambahan adalah 31,94 ± 3,54. Nano Kitosan mampu menambah nilai kekerasan semen ionomer kaca dengan hasil rerata dan standar deviasi sebagai berikut konsentrasi 0,5%= 51,60 ± 9,34 , 1%=91,20 ± 15,09, 1,5%,= 95,22 ± 14,12 dan 2%=117,60 ± 40,90. Hasil uji menggunakan uji One Way Anova didapatkan nilai p = 0,000 sehingga p<0,5 dan dinyatakan terdapat pengaruh yang signifikan antar kelompok konsentrasi terhadap nilai kekerasan semen ionomer kaca. Simpulan: penambahan nanokitosan cangkang kerang hijau dapat meningkatkan kekerasan semen ionomer kaca.